Exploring the Interplay of Metacognitive Awareness and Reading Proficiency: A Study among Moroccan University EFL Students - El Mehdi El Madani; Mohammed Larouz; Mustapha Fagroud; Zayneb Saadallah; Jamal Barebzi (Yayasan Visi Intan Permata, 2024)
In recent years, there has been a considerable interest in metacognition and language learning research. An ever-increasing body of literature shares the consensus that metacognitive knowledge plays a critical role in the process of language learning. While metacognitive knowledge encapsulates being cognizant of one’s own language level and the learning strategies available to improve this level, the absence of such an awareness brings about serious challenges that hinder the process of language learning. In light of such a hiatus, the present study attempts to examine the relationship between EFL university students’ reading proficiency in English and their metacognitive awareness of reading strategies. In order to achieve this objective, Data were collected using three language proficiency tests in reading and Metacognitive Awareness of Reading Strategies Inventory (MARSI). 94 third-year university students enrolled in the Department of English Studies at the School of Arts and Humanities in Meknes formed the sample of this investigation. With reference to data analysis, the study employed Pearson product-moment correlation and Simple Linear Regression as statistical tools to analyze the generated data. The findings of the investigated relationship showed that there was a strong positive correlation between participants’ English reading proficiency and their reading metacognitive awareness, with a r-value of 0.810. It was also revealed reading metacognitive awareness predicted 65% of reading comprehension ability. Finally, the findings of the present study have brought about crucial contributions, in terms of both theory and practice, to the existing body of literature on metacognition and language learning. The results of this endeavour have also triggered various pedagogical and methodological implications and recommendations for language teachers, syllabus designers, higher education departments of English studies, and future research.